Kieliä ja kohtaamisia Turun historiassa Näkökulmia monikielisyyteen - Kolehmainen, Leena; Liira, Aino; Nummila, Kirsi-Maria (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
The present volume is a multidisciplinary collection of research articles exploring language use, language contact and multilingualism in the history of Turku, the first town in Finland, founded around the turn of the fourteenth century. Consisting of an introduction by the editors and nine case studies in the fields of linguistics, history, archeology, and literary and cultural studies, the volume participates in a wider discussion on multilingual communities while offering a closer look into linguistic encounters in Turku and its immediate vicinity. The volume covers the period from the Middle Ages (c. 1100-1500) to the latter half of the twentieth century. The case studies illustrate the wide array of languages, linguistic varieties and registers that the inhabitants and travellers used in their daily lives, the specific contexts in which certain languages were used, and the effects of these linguistic encounters at personal, social or institutional levels.